Enzyme-linked immunosorbent assay as complement of intradermal skin test for the detection of mycobacterium bovis infection in cattle - Garbaccio, Sergio Gabriel; Garro, Carlos Javier; Delgado, Fernando Oscar; Tejada, G. A.; Eirin, Maria Emilia; Huertas, Pablo Sebastian; Leon, Emilio Arnaldo; Zumarraga, Martin Jose (Elsevier, 2019)
Diagnostic tests based on cell-mediated immunity are used in programs for the control and eradication of bovine tuberculosis (bTB), which is mainly caused by Mycobacterium bovis. Additional serological assays could be performed as an ancillary method to detect an infected animal that fails to produce an immune response against the intradermal reaction (IDR), the official bTB test. In this study, we evaluated the effectiveness of an enzyme-linked immunosorbent assay (ELISA) that uses bovine PPD as a capture antigen as a complement to the IDR in herds with confirmed cases of bTB. The study was conducted in two stages. First, a panel of 200 serum samples was analyzed by ELISA. The sensitivity and specificity obtained were 60% and 99%, respectively. The subsequent stage consisted of evaluating 7,494 bovines from 14 selected dairy farms. The number of animals yielding a IDR negative/ELISA positive result were 200. A necropsy analysis of 33 of these IDR negative/ELISA positive animals revealed that 30 (91%) presented granulomatous lesions and positive M. bovis isolation. This finding confirmed bTB in most cases. Altogether, the results obtained in the present study suggest that the combined use of IDR and ELISA is an effective strategy to improve the control of bTB in endemic herds.